2010
DOI: 10.1080/00918360903489101
|View full text |Cite
|
Sign up to set email alerts
|

Victim Blame in a Hate Crime Motivated by Sexual Orientation

Abstract: A jury simulation paradigm was employed for two studies exploring levels of victim blame in a case of bias-motivated assault based on sexual orientation. In the first study, participants were grouped according to their score on the Index of Homophobia (IHP) scale as either reporting high or low support for gay and lesbian community members. The label of the crime (i.e., bias-motivated assault versus first-degree assault) as well as the gender of the victim were systematically varied. Results indicated that att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(55 citation statements)
references
References 36 publications
7
45
2
1
Order By: Relevance
“…Consistent with literature concerning victim blaming and perceptions of victims in hate crimes (e.g., , victim-related beliefs were phrases that refer to beliefs about the victims of hate crimes (e.g., "gay people should/should not be protected" [leveling the playing field] or "the victim was partially responsible for what happened" [victim blaming]). Consistent with literature demonstrating negative perceptions of hate crime offenders (e.g., Plumm, Terrance, Henderson, & Ellingson, 2010), offender-related beliefs were phrases that refer to beliefs about the offenders of hate crimes (e.g., "all deserve to be punished" or "these perpetrators are bigots"). The "other" category included personal reasons, extra-legal factors, study-related reasons, or phrases that did not fit with any of the previous categories.…”
Section: Coding Of Hate Crime-related Beliefssupporting
confidence: 67%
See 1 more Smart Citation
“…Consistent with literature concerning victim blaming and perceptions of victims in hate crimes (e.g., , victim-related beliefs were phrases that refer to beliefs about the victims of hate crimes (e.g., "gay people should/should not be protected" [leveling the playing field] or "the victim was partially responsible for what happened" [victim blaming]). Consistent with literature demonstrating negative perceptions of hate crime offenders (e.g., Plumm, Terrance, Henderson, & Ellingson, 2010), offender-related beliefs were phrases that refer to beliefs about the offenders of hate crimes (e.g., "all deserve to be punished" or "these perpetrators are bigots"). The "other" category included personal reasons, extra-legal factors, study-related reasons, or phrases that did not fit with any of the previous categories.…”
Section: Coding Of Hate Crime-related Beliefssupporting
confidence: 67%
“…For example, while Plumm and Terrance (2013) did not examine whether qualitatively coded statements predicted verdict decisions, frequencies showed that the majority of the legal arguments were made in favor of a not guilty verdict in a hate crime, and most of the morality statements were made in favor of a guilty verdict. Indeed, jurors tend to attribute more blame and punishment in bias-motivated cases (e.g., Cramer, Chandler, & Wakeman, 2010;Plumm, Terrance, Henderson, & Ellingson, 2010). Jacobs and Potter (2000) reasoned that hate crime offenders are viewed as more culpable due to the severe impact on the victims, members of the victim's minority group, and society as a whole.…”
Section: Predictors Of Penalty Enhancement Viewsmentioning
confidence: 99%
“…In fact, it may have been that the scenario used was viewed as unwanted sexual overtures that may have created an implicit threat to a female more so than to a male. Using a similar scenario, however, Plumm, Terrance, Henderson, and Ellingson () found that a case of same‐gender hate crime including an unwanted sexual overture was viewed as a hate crime. Therefore, it is likely that the gender dyad is creating the differential responses in this study rather than the scenario itself.…”
Section: Discussionmentioning
confidence: 99%
“…While antiracial hate crimes have been the center of most research, anti-GLB hate crimes are beginning to gain researchers' interest. The burgeoning literature on lay and student mock juror perceptions of hate crimes against sexual minorities shows two consistent findings: (a) perpetrators of anti-GLB hate crimes are punished and blamed more compared with other types of crimes (e.g., Cramer et al, 2010;Cramer, Wakeman, Chandler, Mohr, & Griffin, in press;Rayburn, Mendoza, & Davison, 2003), and (b) certain participant attitudes influence sentencing and blame judgments of victims and perpetrators in these situations (e.g., Lyons, 2006;Plumm, Terrance, Henderson, & Ellingson, 2010;Rayburn et al, 2003). Perceiver characteristics most relevant to these judgments to date include sexually prejudiced or homophobic beliefs (e.g., Rayburn & Mendoza, 2002), authoritarianism (Cramer et al, in press), and perceptions of the victim (e.g., Plumm et al, 2010).…”
Section: Sexual Orientation and Transgender Hate Crimesmentioning
confidence: 97%